Psychology, religion and spirituality: concepts and applications - Watts, Fraser N. (Cambridge studies in religion, philosophy, and society, 2016)
Concepts and approaches -- Psychoanalysis -- Genetics and evolution -- Brain and cognition -- Religious experience -- Religious practices -- Religious beliefs and thinking -- Spirituality -- Developmental aspects -- Varieties and types -- Health and adjustment -- Personal transformation -- Scripture and doctrine -- Human nature and personality -- Summing-up